2003
DOI: 10.1007/s100380300008
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation associated with inactivation of the SOCS-1 gene, a JAK/STAT inhibitor, in human hepatoblastomas

Abstract: We recently demonstrated inactivation in hepatocellular carcinomas (HCCs) of the gene encoding SOCS1/JAB1/SSI-1, a JAK-binding protein that regulates the JAK/STAT signal-transduction pathway. In a follow-up immunochemical investigation of expression of SOCS-1 in hepatoblastomas (HBLs), the protein was markedly reduced in half of the HBL tumors we examined. CpG-rich regions upstream of the SOCS-1 gene were hypermehylated in 7 of the 15 HBL cases. The results suggest that hypermethylation may play an important r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 24 publications
0
51
0
1
Order By: Relevance
“…Inactivation of phosphatases such as SHP1 or SHP2, which dephosphorylate JAKs and STATs, might explain JAK deregulation. Other hypotheses include inactivation of negative regulators of the JAK-STAT pathway, such as the SOCS proteins, that were shown to be transcriptionally repressed by hypermethylation in different types of cancer (He et al, 2003;Nagai et al, 2003). However, we did not detect any decrease in SOCS1, 2, 3 and CISH expression in the five autonomous clones tested (data not shown).…”
Section: Activated Signaling Pathways In Autonomous Clonesmentioning
confidence: 71%
“…Inactivation of phosphatases such as SHP1 or SHP2, which dephosphorylate JAKs and STATs, might explain JAK deregulation. Other hypotheses include inactivation of negative regulators of the JAK-STAT pathway, such as the SOCS proteins, that were shown to be transcriptionally repressed by hypermethylation in different types of cancer (He et al, 2003;Nagai et al, 2003). However, we did not detect any decrease in SOCS1, 2, 3 and CISH expression in the five autonomous clones tested (data not shown).…”
Section: Activated Signaling Pathways In Autonomous Clonesmentioning
confidence: 71%
“…The present and previous studies evaluated the methylation status of at least 20 genes in hepatoblastoma and found that only 3 genes were methylated (Table IV). 9,34,35 The limited number of methylated genes suggest that this profile may be specific for hepatoblastoma, 38 and the survival and stage distribution analyses disclosed that combined RASSF1A and SOCS1 or CASP8 methylation, or joint methylation of the 3 genes are not correlated with the advanced stage of disease or a poor outcome, contrary to the findings that methylation of multiple genes were correlated with a poor outcome, reported in neuroblastoma. 39 The present multivariate analysis identified unresectable tumor stages of disease (3B and 4) as the most significant factor predicting overall survival, followed by RASSF1A methylation.…”
Section: Discussionmentioning
confidence: 92%
“…After the bisulphate treatment, the samples were amplified both for the promoter and Exon 2 regions by MS-PCR. The primers for the promoter region was reported previously [6] and Exon 2 primers were redesigned by us. The PCR yields were analyzed on 4% agarose gel.…”
Section: Bisulphate Treatment and Ms-pcrmentioning
confidence: 99%
“…Loss of SOCS1 gene could play an important role in the regulation and progression of leukomogenesis in CML. Thus, we aimed to study the methylation status of SOCS1 gene, which has been shown to be methylated in different tumor types [5][6][7], in CML patients.…”
Section: Introductionmentioning
confidence: 99%